PENINGKATAN KREATIVITAS ANAK MELALUI PENGEMBANGAN MEDIA KREATIF DARI BAHAN ALAM PADA RUMAH BELAJAR - UTOMO, YUDHI; YUDHA TRIWAHYUNI , RATRI; NURFADILLAH , RESTIN; DEWI ZUHRIYAH , UTIY; WAHYU SEPUTRI , VIA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Science and technology continue to develop over time. The field of education is also adapting to these advancements, one of which is by preparing an excellent future generation. To cope with these developments, children need skills that can be nurtured, one of which is creativity. Every child has the potential for creativity that can be developed. Creativity helps children innovate in various situations and is one of the essential skills that support their success in pursuing further education. However, children's creativity does not grow on its own; it needs to be further cultivated. The purpose of this study is to prove that the development of creative media using natural materials can be a solution to training children's creative thinking skills. This study employs a quasi-experimental research method conducted on a single experimental group, consisting of 20 children from the